AGENIASP1S CITRICOLA (HYMENOPTERA: ENCYRTIDAE), PARASITOIDE ESPECÍFICO DE PHYLLOCNISTIS CITRELLA (LEPIDOPTERA: GRACILLARIIDAE): INTRODUCCIÓN Y DATOS PRELIMINARES SOBRE SU DESEMPEÑO EN LA ARGENTINA (Acta Entomológica Chilena, 2022)
A. citricola was fortuitously introduced in Argentina, probably together with it host. Nevertheless, thisspecies was introduced again in citrus orchards from Perú. A key to sepárate the two species of Ageniaspisknown for Argentina and bibliography on life history and use in biological control are provided. Dataabout the performance of this exotic species are compared with that of native parasitoids.